Comparative analysis of diet effects on growth performance and nutrient composition in house cricket, Acheta domestica as an alternative protein source in Thailand - Suphawadee Yaemkong; Tossaporn Incharoen; Nontaporn Rattanachak; Touchkanin Jongjitvimol (Cogent Food & Agriculture)
This comprehensive study investigated the diet’s impact on the growth and nutritional value of crickets (Acheta domesticus) in northern Thailand across five feed treatments. These included a commercial formula (CF21) with 21% protein content as a control, a novel cycling program of commercial formula (CF14) alternating between 21% and 14% protein feeds, and three new formulas (NF) with varied protein compositions (NF21 maintained a 21% protein diet, while NF17 and NF14 transitioned to 17% and 14% protein, respectively, after 21 days). Results revealed variations (p < 0.05) in production efficiency for 42-day-old crickets, including body weight, cricket production weight, and feed-to-body-weight conversion efficiency. NF21 displayed the highest average body weight for both sexes but the lowest total production weight. CF14 outperformed CF21 and the three new formulas. Despite trends in NF17 and NF14, their total weights slightly trailed CF14. Survival rates correlated with diet composition, with CF14 having the highest rate (71.08%), while subsequent groups experienced diminishing survival rates. Feed conversion ratio (FCR) analysis showed disparities, with NF21 recording the highest FCR value (3.34 ± 0.02) and CF14 recording the lowest (2.35 ± 0.01), highlighting different diet efficiencies. Economically, NF14 demonstrated cost-effectiveness at 25.92 ± 0.15 THB/kg (1 THB = 0.025 EUR), while CF14 emerged as the leader, achieving the highest net profit with a 51.51% cost reduction. The nutrient composition study revealed no significant impact on six values across all treatments. Overall, the majority of results favored CF14 as the preferred choice for achieving both cost-effectiveness and maximum yield.